Informality, Job Quality, and Welfare in Sri Lanka - World Bank (World Bank, Washington, DC, 2020)
Informal employment remains a salient and persistent feature of the Sri Lanka labor market, with around 70 percent of the work force informally employed. There are generally three reasons to be concerned about high informality: poverty, productivity and public finance. This report focuses on the poverty and vulnerability aspect of informal employment, by showing that informal jobs are more precarious in nature than formal jobs and are associated with inferior working conditions and lower earnings. The three key messages of the report are as follows. First, The quality of informal jobs is much lower than that of formal jobs. Informal workers have more precarious employment arrangements and inferior working conditions. Their low earnings levels elevate the risk of poverty. Second, Stringent labor laws, along with the high cost of compliance and complexity of labor regulations, have encouraged informality. But formalization does not necessarily ease other constraints such as access to credit, reducing the incentive to formalize. Third, Reducing informality should not be in itself a policy goal. Reforms should focus on regulatory reforms that aim to reduce the cost and increase the benefits of formality, as well as on measures that enhance productivity.